Environmental Nanotechnology Volume 1 (Environmental Chemistry for a Sustainable World,, 2018)
This book presents the environmental benefits of nanomaterials in agriculture, water purification and nanomedicine. Nanotechnology will modify the environment both in a positive and negative way. On the one hand, new nanomaterials are promising for reducing greenhouse gases, cleaning toxic wastes and building alternative energy sources. On the other hand, some toxic nanoparticles enter and disrupt ecosystems. Therefore, research should focus on the sustainable use of nanomaterials to avoid environmental contamination. This volume is the first of several volumes on Environmental Nanotechnology, which will be published in the series Environmental Chemistry for a Sustainable World.